Modification of optical properties of tungsten exposed to low-energy, high flux deuterium plasma ions - Alimov, V.Kh.; Belyaeva, A.I.; Galuza, A.A.; Isobe, K.; Konovalov, V.G.; Savchenko, A.A.; Slatin, K.A.; Solodovchenko, S.I.; Voitsenya, V.S.; Yamanishi, T. (Вопросы атомной науки и техники, 2011)
Anomalous change of optical properties of recrystallized W caused by exposure to D plasma ions at sample temperature of ~535 K was studied by ellipsometry and reflectometry. There is a qualitative difference between the samples reflectivity values measured directly and calculated using ellipsometric data. A physical model of the phenomenon is suggested. It is shown that on the W surface exposed at ~535 К two processes take place 1) blistering and 2) modification of electron structure in the upper-most layer.